Influence of alpha(S1)-casein and kappa-casein polymorphism on the curd yield of Italian Mediterranean buffalo (Bubalus bubalis L.) milk - Zicarelli, Luigi; Di Palo, Rossella; Napolano, Roberto; Tonhati, Humberto [UNESP]; De Carlo, Ester; Gagliardi, Rosa; Di Luccia, Aldo; la Gatta, Barbara (Elsevier B.V., 2020)
The influence of alpha(S1)-casein (alpha(S1)-CN) and kappa-casein (kappa-CN) polymorphism on the curd yield and 12 other parameters of milk obtained from 89 Italian Mediterranean buffaloes (IMB) was evaluated. IMB milk carrying alpha(S1)-CNB and kappa-CNX1 variants resulted in a greater curd yield. For these variants, the greater efficiency was attributable to higher content of proteins but not to milk production. In addition, the greater efficiency in curd yield of IMB milk carrying kappa-CNX1 (P < 0.05) or alpha(S1)-CNB (P < 0.05) was characterised by a higher real curd yield/estimated curd yield (RCY/ECY) ratio. The IMB milk that exhibited the lowest value of RCY contained the kappa-CNX1X2 and alpha(S1)-CNAB heterozygotes and kappa-CNX2 and alpha(S1)-CNA homozygotes. IMB milk carrying kappa-CNX1 and alpha(S1)-CNB, which presented the highest RCY, can be translated into an economic advantage if milk remuneration was done on the actual yield. (C) 2019 Elsevier Ltd. All rights reserved.